Students of the Middle Urals: The Transformation from Classical to Digital Community (Research Prospects) - Narkhov, Dmitry Yu.; Narkhova, Elena N.; Vishnevsky, Yu. R. (KnE Social Sciences, 2021)
Students are one of the most studied communities within the sociology context and especially the youths’ sociology and the sociology of education. Today, students are viewed both as the intellectual avant-garde force, leaders of social initiatives of the Russian youths and as a specific educational community. This study is based on the traditional method of document analysis, which allows us to identify key fields of the research. The research is devoted to the problems of changing students in the information society. The authors substantiate the need and prospects for studying students as a ’digital community’. A review of the social, political, sociocultural and other aspects of comprehensive students was conducted. Keywords: Actual culture, modernization of higher education, social transformation, social resource, students, digital community